2008
DOI: 10.1088/0953-2048/21/4/045007
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of superconductive passive phase shifters in high-speed integrated RSFQ digital circuits

Abstract: The reduction of the critical current density in rapid single-flux quantum (RSFQ) circuits enables new application fields, like quantum computing and photonic detector readout. The low current density fabrication process creates new design challenges, such as lower stability against thermal fluctuations, violation of the lumped elements condition for microstrip inductances and increased sensitivity to the technological spread. To overcome these issues, we suggest a passive phase shifter as a promising alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…It is anticipated that unconventional junctions either with a fixed phase shift ϕ 0 (ϕ-junctions), or with an in-built spatial phase variation along the junction ∆ϕ (0 − ϕ junctions) may provide additional functionality in Josephson electronics [1][2][3][4]. For example, they can operate as autonomous and persistent phase batteries -one of key elements of quantum [1,[5][6][7][8][9][10][11][12][13][14] and digital Josephson electronics [2,3,15,16]. Such junctions can be also used for development of novel types of cryogenic memory [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is anticipated that unconventional junctions either with a fixed phase shift ϕ 0 (ϕ-junctions), or with an in-built spatial phase variation along the junction ∆ϕ (0 − ϕ junctions) may provide additional functionality in Josephson electronics [1][2][3][4]. For example, they can operate as autonomous and persistent phase batteries -one of key elements of quantum [1,[5][6][7][8][9][10][11][12][13][14] and digital Josephson electronics [2,3,15,16]. Such junctions can be also used for development of novel types of cryogenic memory [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Such junctions can be also used for development of novel types of cryogenic memory [17][18][19][20][21][22]. The π-phase shift is most commonly needed, e.g., for bringing the flux-qubit to the degeneracy point [1,[5][6][7], for realization of complementary digital Josephson electronics [2,3,15,16] and for maximum distinction between 0 and 1 state in a memory cell [17].…”
Section: Introductionmentioning
confidence: 99%
“…Josephson junctions [45][46][47][48][49]. Even for conventional RSFQ circuits, the improved operational margins, bit-error rates, and gate memory non-volatility were reported [50][51][52][53].…”
Section: Magnetically Biased Esfq Shift Register (Mesr)mentioning
confidence: 99%
“…Similar phase shifters have been used for digital RSFQ electronics. 14 , 15 Recently it was shown that an Abrikosov vortex can induce a JPS in nearby JJs in the full [−2π, + 2π] range. 23 , 43 , 44 Since vortices can be easily manipulated (displaced, introduced, or removed) by magnetic field, H , 23 , 45 47 current, I , 20 , 48 , 49 and light, 50 , 51 they can be used for creation of memory cells 20 and tunable phase shifters.…”
Section: Introductionmentioning
confidence: 99%